EVALUATION OF ANTIHISTAMINIC ACTIVITY OF DOLICHOS BIFLORUS - ANUPAMA A. SURALKAR; SANJAY B. KASTURE (International Journal of Pharma and Bio Sciences, 2013)
Dolichos biflorus Linn. (Family- Fabaceae) is commonly known as ‘Horse gram’. The seeds are used in the treatment of piles, pain, constipation, wounds, urinary calculi, cough, edema, and asthma. The present study was therefore designed for evaluation of antihistaminic activity of seeds of Dolichos biflorus in the management of asthma. Antihistaminic activity of ethanolic extract of Dolichos biflorus seeds (DB) was evaluated by using histamine induced contraction on goat tracheal chain preparation and histamine induced bronchoconstriction in Guinea pigs. The ethanolic extract of Dolichos biflorus seeds (DB) significantly inhibited histamine induced contraction of isolated goat tracheal chain preparation and significantly protected the guinea pigs against histamine induced bronchospasm as indicated by delay in the preconvulsive dyspnoea time (PCT) following the exposure of histamine aerosol. The results suggest that ethanolic extract of Dolichos biflorus seeds (DB) has antihistaminic activity and may prove beneficial in the management of asthma.